The use of MOOCs in learning English: Rwaq as an example - Althubaiti, Sultan Saleem; Almasaad, Ahmad Zaid (Journal of Educational and Psychological Sciences, 2020)
This study aimed to examine how effective using MOOCS in learning English, and how a number of factors, such as age, gender, education level, occupation and number of courses taken, can influence this effect, if any. In particular, this study sought to answer the following question: To what extent the use of MOOCS can enhance English learning?A number of English learners (n = 336) were recruited from an online English course initiative (English Mastery) at Rawq (An Arabic online platform offering open courses). Two sets of questionnaire were distributed among the learners. The first set was designed to obtain some demographic information from the participants (age, gender, education level, occupation, and number of Rwaq English Mastery courses taken). The second set contained 33 items designed to examine whether the learners benefited from the offered online English courses in terms of both: knowledge and skills.The results indicate that the use of the online English courses provided by the English Mastery Initiative at Rawq was effective in increasing the learner’s knowledge and skills of the English language. The factors age, gender, education level, and occupation were found not to have any effect on the results. Only the number of online courses taken was found to be effective in enhancing the learners’ knowledge and skills of the English language (from 3 to five courses).The study recommends the following: 1) online English language courses at Rwaq should be increased in number, 2) Rwaq should survey English leaners’ needs before offering their courses, 3) Rwaq should offer courses specialized in training English learners for taking standardized English language tests (e.g., IELTS, TOEFL, STEP), and 4) Saudi Universities should have their own MOOCs.
Keywords: MOOCs; educational platform; online learning; English language learning and teaching